The Syntheses and Vibrational Spectra of O-16- and O-18-Enriched cis-MO2 (M=Mo, W) Complexes - Anssi Peuronen; Reijo Sillanpaa; Ari Lehtonen (WILEY-V C H VERLAG GMBH, 2022)
In this contribution, we report convenient synthetic approaches for obtaining O-16/O-18-enriched dioxidometal(VI) complexes, MO2(L) (W, Mo), with a linear, tetradentate amine phenolate ligand N,N-dimethyl-N,N-bis(2-hydroxy-3,5-dimethylbenzyl)ethylenediamine (H2L) and describe their characterization by IR and Raman spectroscopy complemented by DFT computational analysis. The isotopologues of WO2(L) were made of tungsten(VI) trisglycolate W(eg)(3) (eg=1,2-ethanediolate dianion) and ligand H2L in the presence of either H-2[O-16] or H-2[O-18], whereas (MoO2)-O-16(L) was made using Na(2)MoO(4)2H(2)O which was converted to (MoO2)-O-18(L) by oxido substitution using H-2[O-18]. The complementary IR and Raman analyses show the (MO2)(s) and (MO2)(a) at 934 and 899cm(-1) for (WO2)-O-16(L) and at 914 and 898cm(-1) for (MoO2)-O-16(L), respectively. In the vibrational spectra of the O-18 substituted derivatives, the (MO2)(s) were shifted to lower energy by 43cm(-1) for (WO2)-O-18(L) and by 41cm(-1) for (MoO2)-O-18(L) whereas asymmetric MO2 stretches in the IR were partially overlapped by an organic ligand related stretch. However, Raman spectroscopy, accompanied by DFT calculations, allowed the deciphering the (MO2)(a) shifts of 47cm(-1) for (WO2)-O-18(L) and 31cm(-1) for (MoO2)-O-18(L).